The Dynamics of Islamic Inheritance in Indonesia Between Sharia and Social Realities - Ritonga, Raja; Ritonga, Mahyudin (Universitas Muhammadiyah Surabaya, 2024)
This research examines the dynamics of Islamic inheritance in Indonesia, focusing on the interaction between sharia principles and the diverse social realities in various Muslim communities. Indonesia, as the country with the largest Muslim population in the world, offers a unique context in which Islamic inheritance law must adapt to various cultures, customs, and national legal systems. This study aims to identify how sharia provisions on inheritance are applied and adjusted in the inheritance practices prevalent in society. The method used in this research is a form of library research. Library research is conducted by collecting data through the analysis of relevant literature related to the study's theme. This research employs a qualitative approach with a descriptive-analytical method. The results of the study show that although sharia principles provide a clear legal framework, their implementation often needs to be adjusted to local social norms to achieve justice and welfare. Additionally, it emphasizes the importance of flexibility and contextualization in the application of Islamic law, as well as its potential contribution to social harmony and justice in a multicultural society.